Peran Hukum Perdata Internasional dalam Sengketa Merek Dagang: Studi Kasus Astra Honda Motor vs Trek Bicycle Corporation - Sulistianingsih , Dewi; Felix Kusbintoro, Arsenius (Zaaken: Journal of Civil and Business Law, 2025)
This study examines the role of Private International Law in resolving the trademark dispute between PT Astra Honda Motor (AHM) and Trek Bicycle Corporation (TBC) concerning the “Marlin” trademark. Using a normative juridical approach, the research relies on secondary data such as legislation, legal documents, and relevant literature. The findings reveal that Private International Law plays a strategic role in providing certainty regarding jurisdiction, applicable law, and cross-border intellectual property rights protection. The application of the principles of choice of law and choice of forum serves as a key mechanism in determining the governing law and the competent forum to adjudicate disputes. This research underscores the importance of a comprehensive understanding of Private International Law for legal practitioners and policymakers in addressing the complexities of globalization. Practically, it recommends that multinational companies adjust their legal strategies to accommodate differences in legal systems and intellectual property standards across jurisdictions, thereby ensuring effective trademark protection and adaptation to the evolving international legal environment